(3GdHQgGf Ydi Yed MHT aj eWGdY GdSeJ aj RjLIs - (3efUhQ Hf Ydj Hf YQGb, CHh fUQ,J (B425 (3g` s
(3ChdgG (B:s
(3EJVM di (B_ (3CjOc Gddg (B_ (3CeQ MSGH eWGdY GdSeJ ef LOGhd GdJbhje CTZd eG cfJ Yfg NGWQkG Yde Gddg HPdc hCJjJ eG hVM di hHGOQJ HMedg Edjc dJdMbg HehVYg ef GdebGdI GdKGdKI s
(3BNQgG (B:s
(3hEPG UGQ (B( (3eg (B) (3eYdhekG , Hbi (B( (3e (B) (3eYdhekG agPG gh GdWQjb ai eYQaI eWGdY GdSeJ ef LOhd GdJbhje (B( (3dG(B) (3GdChd , hPdc eG CQOfG HjGfg JeJ GdQSGdI , hGddg eMehO Ydi cd MGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B99(3C (B- (3U(B100(3Cs
(3HgG CTcGd gfOSjIs
(3QSGdI HYK HgG Edi CHj GdQjMGf eMeO Hf CMeO GdHjQhfi GdeJhai SfI (B440 (3hMHT gh CMeO Hf YHO Gddg GdMGSH GdeQhRi GdeYQha HMHT GfXQ SRcjf (B6/173s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs